(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
Rakhaldas Banerjee is a brilliant figure in 20th century Indian history. The discovery of Mohenjodaro brought his worldwide fame. In addition to various archaeological activities, his contribution in uncovering the past art history of the country is undeniable. In the initial phase, Western writers played the role of pioneers in uncovering various aspects of the history of ancient India. Pursuing their initiative, the Indian scholars vowed to restore the history of their country. Rakhaldas Banerjee’s inner heart was enlightened by the Indian Scholars. As a result, he flourished the world of Indian art historiography and Gaudiya art philosophy. After the fall of the Gupta empire, two kingdoms named Gaur and Banga emerged, Gaur kingdom was formed with North Bengal and West Bengal in general and Bengal or Samatata kingdom was formed with parts of East and West Bengal. Sometimes South Bengal was included in the Gaur kingdom. But Rakhaldas thinks that all the provinces from the foothills of Himachal to the Bay of Bengal were called ’Gaudesh’ or ’Gaudrajya’ till the twelfth century. Immediately after the rise of the Pala administrative system in the mid-eighteenth century, a new style of art developed in Bangladesh, known as Gaudiya Art. In addition to greatly expanding in the neighbouring states this style of art spread its influence and gave rise to different styles of art. Rakhaldas Bandyopadhyay referred to the art style of the Chaitanya period as enlightened by the spirit of Vaishnavism as the ’art of the Indian genre’. But the progress of this ’art genre’ was not uniform. Although this art developed its own genre within a short period of time, Gaudiya art lost much of its luster due to the anarchic situation created after Shashanka’s death. The political stability brought about by the establishment of the Pala regime in the mid-8th century led to the flourishing of Gaudíya art. However, this art began to decline during the Post-Devapal period. In the second phase of the art i.e. from the 10th to the 11th century, this art did not flourish but progressed through various changes. In the Sena period, the slender body of the statue was replaced by fleshy fat, which made it quite different from the earlier period. A swoon of pure poetic exhilaration took place in the statue’s body, but it was only momentary. Its artistic glory was destroyed by the invasion of foreign powers. There is no denying that Rakhaldas Banerjee paved the way for Indian art practice, which was later followed by many artists and Indian litterateurs. As a result, Indian and Bengali history and literary fields were enriched.